TANGGUNGJAWAB INDERA MANUSIA DALAM MENERIMA INFORMASI: QS. AL-ISRA’ AYAT 36 - Siti Husnul Khotimah; Mahda Aulia; Nur Aisyah Athirah binti Safian; Ahmad Mujahid (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
This study explores the role and moral responsibility of human senses in receiving information, based on the perspective of the Qur’an, particularly Surah Al-Isra’ verse 36. Employing a qualitative, library-based research method, this paper integrates Islamic epistemology and cognitive science to examine how sensory faculties such as hearing, sight, and the heart (understood as the locus of reasoning and perception) are considered divine trusts that will be held accountable. The Qur’anic directive underscores the imperative of verification (tabayyun) and intellectual responsibility in processing information, especially amidst the challenges of misinformation in the digital age. Drawing from the scientific exegeses of contemporary scholars like Shaykh Tantawi Jauhari, Prof. Dr. Zaghlul An-Najjar, and Prof. Dr. Abdul Karim Bazyar, this research highlights the Qur’anic alignment with empirical and rational inquiry, emphasizing observation, analysis, and accountability as core principles of knowledge acquisition. Furthermore, the study analyzes the concept of sensory epistemology in both Islamic and scientific discourses, stressing the ethical dimension of sensory use. The findings affirm that Islam not only recognizes the biological function of the senses but also their moral and spiritual implications, making ethical information management a key component of Islamic ethics. This study concludes that responsible utilization of sensory faculties is essential in cultivating a knowledgeable, discerning, and morally conscious society.